A research on consanguineous marriages of women who are settled and gave birth in the hospitals in Elazig City center - Pirinçci, Edibe; O?uzöncül, Ferdane; Açik, Yasemin (My University, 2002)
In the research on women who gave birth to find out the frequency of marriages to relatives that was conducted in the hospitals in the Centrum of Elazi?, out of 1047 women who gave birth between 1st February and 25th March 500 women-approximately half of the total number- was taken into account. 28.8% of 500 marriages (114) are consanguineous, and the proportion of first degree consanguineous marriages is %67.5. 27.6% of these women who are married to their close relatives are illiterate and 25.4% are primary school graduates. It was found out that the average of marriage first age for women married to their relatives is 20.0 (SD=3.7) and for men married to their relatives is 23.9 (SD=4.2), whereas it is 21.1 (SD=4.1) for women and 25.7 (SD=5.6) for men married to people apart from their relatives (p>0.05). When still-born cases of infants are considered, the percentage is 20.2% for the relative couples; however it is 8.8% for the other group of couples. Furthermore, at their last childbirth, the frequency of the cases of the infants' death at their early ages is 3.5% for the couples married to their relatives whereas it is 0.8% for the others (p<0.05). To sum up, because of the fact that marriages in relatives' being widespread in Elazi? is still a considerable problem, youngsters at the age of marriage and their parents should be educated and serviced with fundamental health services about the subjects like the inconveniences of marriages in relatives and the vitality of genetic consultations.
Elazi? i?l merkezindeki hastanelerde do?um yapan ve i?l merkezinde i?kamet eden kadinlarda akraba evliliklerinin i?ncelenmesi
Keywords: Consanguineous marriage; Hospital